2015
DOI: 10.2174/1389202916666150317233103
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Molecular Genetics of Non-syndromic Syndactyly

Abstract: Syndactyly, webbing of adjacent digits with or without bony fusion, is one of the most common hereditary limb malformations. It occurs either as an isolated abnormality or as a component of more than 300 syndromic anomalies. There are currently nine types of phenotypically diverse nonsyndromic syndactyly. Non-syndromic syndactyly is usually inherited as an autosomal dominant trait, although the more severe presenting types and subtypes may show autosomal recessive or X-linked pattern of inheritance. The phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Based on the anatomic position of the additional digits, polydactyly can be classified into preaxial polydactyly (PPD), postaxial polydactyly and central polydactyly [3]. Previous pathological researches have shown that most of the PPD abnormal cases follow an autosomal dominant inheritance pattern and a few express an autosomal recessive pattern of inheritance [4]. In addition to high incidence in humans, there is high morbidity rate in pigs, cats, chickens and other vertebrates [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the anatomic position of the additional digits, polydactyly can be classified into preaxial polydactyly (PPD), postaxial polydactyly and central polydactyly [3]. Previous pathological researches have shown that most of the PPD abnormal cases follow an autosomal dominant inheritance pattern and a few express an autosomal recessive pattern of inheritance [4]. In addition to high incidence in humans, there is high morbidity rate in pigs, cats, chickens and other vertebrates [5].…”
Section: Introductionmentioning
confidence: 99%
“…[31], TWIST1 [32], PITX1 [33] etc. and reviewed in Malik et al [2] and Deng et al [4]. Among all of these identified candidate genes, majority of them are involved in the SHH signaling pathway or ciliogenesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Webbing of adjacent digits with or without bony fusion is termed as syndactyly and it is a common hereditary limb anomaly. It can occur either as an isolated malformation or as a component of a syndromic diagnosis and more than 300 associated syndromes have been identified [ 18 ]. Oligosyndactyly is one of the syndactyly phenotypes and it is a frequent feature in several syndromes, namely, CLS syndrome, fibular aplasia, tibial campomelia and oligosyndactyly (FATCO) syndrome, fibular hemimelia (FH), Cornelia de Lange (CdL) syndrome and chromosome 2q35 duplication syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsyndromic syndactyly manifests itself as 9 distinct types; at least 11 loci and 8 relevant genes have been identified 27 (Fig. 1 ).…”
Section: Nonsyndromic Dactylies: Phenotypes and Geneticsmentioning
confidence: 99%